Advantages and Risks of New Forms of Employment in Conditions of Development of the Digital Economy - Nasimov, Dilmurod; Artikov, Zokir (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The article discusses the trends in the transformation of the labor market under the influence of a change in HR management. It analyzes new forms of interaction between the employer and the employee. Considers the best experiences of the remote work. The advantages of remote work from the point of view of employees and employers are studied. In addition, it proposes directions and conclusions for further the development of new forms of employment.